Facing the Inevitable: Being Prepared for Regulatory Requirements for Laboratory Developed Tests. Issue 6 (5th April 2018) - D'Angelo, Rita; Weiss, Ronald; Wolfe, David; Chinnam, Ratna; Murat, Alper; Gluesing, Julia; Somers, Toni
Abstract: Objectives: We introduce regulatory terms, definitions, and the Quality System Regulation as proposed by the US Food and Drug Administration in the 2014 draft guidance entitled Framework for Regulatory Oversight of Laboratory Developed Tests and explore medical device requirements applicable to a laboratory environment to design, develop, and validate laboratory developed tests (LDTs). Methods: We performed nine interviews with laboratory professionals to explore concerns and challenges regarding the draft, translated the results into operational factors, and surveyed professionals to test the factors that would comprise a regulatory quality management system framework. Results: Nine interviewees and 35 survey respondents shared concerns of risk classification, process validation, patient safety, and general ambiguity regarding the proposed requirements for development of LDTs. Conclusions: Respondents agree that a regulatory quality management system is needed in laboratories that develop LDTs, but the translation and method for design control to a clinical laboratory do not exist. As a result, laboratories are taking the wait-and-see approach.